INNOVASI PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULUKUMBA DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Syafruddin, Wafiq Arizah; Ilyas, Musyfikah; Aisyah, Siti (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
his study aims to describe Public Service Innovations for Persons with Disabilities at the Population and Civil Registration Office of Bulukumba Regency in the Siyasah Syariyyah Perspective. In answering these problems, the author uses a normative syar’i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the study show that the Real Laraku Innovation made by the Population and Civil Registration Office of Bulukumba Regency has provided many conveniences for persons with disabilities because of the service provided, namely the Pick Up Ball service. This service goes directly to the villages, to provide a service for persons with disabilities. Not only that, but the Population and Civil Registration Office of Bulukumba Regency has collaborated with the Health Office, Social Services, Health Centers, Village Heads to find out the whereabouts of persons with disabilities, the facilities they have are also quite helpful in making it easier for persons with disabilities. In Siyasah Syariyyah’s view, the public services provided must be the same. As stated in QS. At-Tin verses 4-6 and Qs. Ar-Ra’d verse 11 which invites to make a change for the better.